2018
DOI: 10.1021/acs.chemrestox.8b00194
|View full text |Cite
|
Sign up to set email alerts
|

N–O Reduction and ROS-Mediated AKT/FOXO1 and AKT/P53 Pathways Are Involved in Growth Promotion and Cytotoxicity of Cyadox

Abstract: Cyadox is a novel derivative of quinoxaline-1,4-dioxides (QdNOs) with the potential to be developed as a feed additive. However, the pharmacological and toxicological bioactive molecules of cyadox and the molecular mechanism of its pharmacological and toxic actions remain unclear. In the present study, cyadox and its main metabolites of cy1, cy4, cy6, and cy12 were selected; the growth promotion characteristic was indicated by the mRNA level of EGF; and the cytotoxicity of cyadox was determined by methylthiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We have already found that cholesterol upregulates ROS levels in TDSCs [11]. ROS affect a variety of signaling pathways, including the AKT/ FOXO1 signal pathway [19]. The activation of AKT promotes cell growth and proliferation and increases cell resistance to apoptosis in many cell types [20].…”
Section: Introductionmentioning
confidence: 99%
“…We have already found that cholesterol upregulates ROS levels in TDSCs [11]. ROS affect a variety of signaling pathways, including the AKT/ FOXO1 signal pathway [19]. The activation of AKT promotes cell growth and proliferation and increases cell resistance to apoptosis in many cell types [20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, quite many studies have suggested that cyadox can improve the growth performance of animals including pigs and poultry [6,7,[37][38][39][40]. Antimicrobials including cyadox might in uence growth via an endocrine axis such as IGF-1, GH and epidermal growth factor (EGF) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Quinoxaline, 1,4-dioxide derivatives (QdNOs), consisting of one or two acyclic chain moieties combined with a quinoxaline ring, are antibacterial and growth promoting agents and have a wide range of biological properties, including antibacterial, antitubercular, anticancer, anti-candida, and antiprotozoal [1][2][3][4][5][6][7]. Previous reports suggest that these drugs can alter intestinal micro ora, improve protein utilization, and increase protein synthesis in vivo [1].…”
Section: Introductionmentioning
confidence: 99%
“…TK is required for cancer growth because of its ability to affect the production of NAPDH to counteract oxidative stress . Our findings demonstrated that the reactive oxygen species (ROS) was generated from N‐O reduction of cyadox in L02 cells (normal human liver cells) and cyadox upregulates EGF expression by the ROS and activating Akt signaling . We inferred that ROS from the metabolism of cyadox might also promote the TK expression besides EGF and both were involved in growth promotion of cyadox.…”
Section: Discussionmentioning
confidence: 99%